Pengaruh Kompetensi Sumber Daya Manusia, Pemanfaatan Teknologi Informasi, dan Training Kerja Karyawan terhadap Kualitas Laporan Keuangan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the impact of human resources (HR) competencies, the utilization of information technology (IT), and employee training on the quality of financial reports at PT Pupuk Indonesia Holding Company. High-quality financial reports are crucial for decision-making within the company, and accurate and reliable reports are necessary for overall company performance. Therefore, this research focuses on assessing how these factors influence the quality of financial reporting within the company. The study adopts a quantitative approach with data collection through surveys. A questionnaire was distributed to 37 accounting staff members at PT Pupuk Indonesia Holding Company to gather data on HR competencies, IT utilization, employee training, and the quality of financial reports produced. Data analysis was performed using linear regression to test the relationships between the variables. The analysis results show that HR competencies and IT utilization have a positive and significant impact on the quality of financial reports. This indicates that improving employee skills and knowledge, along with optimizing the use of information technology systems, can enhance the quality of the financial reports generated by the company. On the other hand, employee training did not have a significant effect on the quality of financial reports. This may be due to the lack of relevance between the training material provided and the practical needs of daily work. These findings highlight the importance of focusing on improving employees' competencies in accounting and better utilization of IT systems to produce more accurate and efficient financial reports. The company should consider developing more advanced information systems and providing training that is more relevant to the needs of the job in order to improve the quality of the financial reports produced.